Capabilities and Limitations of Local Strategies in Dynamic Networks - Götte, Thorsten; Knollmann, Till; Meyer auf der Heide, Friedhelm; Scheideler, Christian; Werthmann, Julian (On-The-Fly Computing -- Individualized IT-services in dynamic markets)

Zur Darstellung der Afrikanischen Europäerin in Geschichte und Gegenwart - Sharon Dodua Otoos Roman 'Adas Raum' - Müller, Inez (Interkulturelle Konstellationen in Literaturwissenschaft und Literaturdidaktik. Festschrift für Michael Hofmann)

Politisches Graffiti (Kunst und Politik)

Virtual On-Demand Volunteer System Based on Delaunay Triangulation - Ashri, Nivedita

Arm und ausgegrenzt. Kinderarmut in der Literatur und im lesenden Klassenzimmer. - Kruse, Iris; Terhorst, Sarah („So viel Größenwahn muss sein!”)

"So viel Größenwahn muss sein!". Zur Einführung. - Kruse, Iris; Kanning, Julian (So viel Größenwahn muss sein! Kinderliteratur, Schule und Gesellschaft. Zum Bildungsauftrag des Literaturunterrichts in der Grundschule.)

Computing and Compressing Electron Repulsion Integrals on FPGAs - Wu, Xin; Kenter, Tobias; Schade, Robert; Kühne, Thomas; Plessl, Christian (2023 IEEE 31st Annual International Symposium on Field-Programmable Custom Computing Machines (FCCM))
The computation of electron repulsion integrals (ERIs) over Gaussian-type orbitals (GTOs) is a challenging problem in quantum-mechanics-based atomistic simulations. In practical simulations, several trillions of ERIs may have to be computed for every time step. In this work, we investigate FPGAs as accelerators for the ERI computation. We use template parameters, here within the Intel oneAPI tool flow, to create customized designs for 256 different ERI quartet classes, based on their orbitals. To maximize data reuse, all intermediates are buffered in FPGA on-chip memory with customized layout. The pre-calculation of intermediates also helps to overcome data dependencies caused by multi-dimensional recurrence relations. The involved loop structures are partially or even fully unrolled for high throughput of FPGA kernels. Furthermore, a lossy compression algorithm utilizing arbitrary bitwidth integers is integrated in the FPGA kernels. To our best knowledge, this is the first work on ERI computation on FPGAs that supports more than just the single most basic quartet class. Also, the integration of ERI computation and compression it a novelty that is not even covered by CPU or GPU libraries so far. Our evaluation shows that using 16-bit integer for the ERI compression, the fastest FPGA kernels exceed the performance of 10 GERIS ($10 × 10^9$ ERIs per second) on one Intel Stratix 10 GX 2800 FPGA, with maximum absolute errors around $10^{-7}$ - $10^{-5}$ Hartree. The measured throughput can be accurately explained by a performance model. The FPGA kernels deployed on 2 FPGAs outperform similar computations using the widely used libint reference on a two-socket server with 40 Xeon Gold 6148 CPU cores of the same process technology by factors up to 6.0x and on a new two-socket server with 128 EPYC 7713 CPU cores by up to 1.9x.

"Tankrabatt" und "Freiheitsenergie". Wie der Blog "neusprech.org" politische Euphemismen entlarvt - Tophinke, Doris (Zwischen Fake und Fakt)

Annotation uncertainty in the context of grammatical change - Merten, Marie-Luis; Wever, Marcel; Tophinke, Doris; Geierhos, Michaela; Hüllermeier, Eyke (International Journal of Corpus Linguistics)

My first contact with the Foodsharing Initiative - Vochatzer, Stefanie (Creative Approaches to Climate and Peace Education. An Educationr’s Guide to Using Storytelling and Art)

Home (Office) is where your Heart is - Marx, Julian; Stieglitz, Stefan; Brünker, Felix; Mirbabaie, Milad (Business & Information Systems Engineering)
Abstract Working conditions of knowledge workers have been subject to rapid change recently. Digital nomadism is no longer a phenomenon that relates only to entrepreneurs, freelancers, and gig workers. Corporate employees, too, have begun to uncouple their work from stationary (home) offices and 9-to-5 schedules. However, pursuing a permanent job in a corporate environment is still subject to fundamentally different values than postulated by the original notion of digital nomadism. Therefore, this paper explores the work identity of what is referred to as ‘corporate nomads’. By drawing on identity theory and the results of semi-structured interviews, the paper proposes a conceptualization of the corporate nomad archetype and presents nine salient identity issues of corporate nomads (e.g., holding multiple contradictory identities, the flexibility paradox, or collaboration constraints). By introducing the ‘corporate nomad’ archetype to the Information Systems literature, this article helps to rethink established conceptions of “home office” and socio-spatial configurations of knowledge work.
Keywords: Information Systems

»In der Art von Inschriften«. Emblematische Inschriftendichtung als Darstellungsprinzip von Ferdinand von Fürstenbergs Monumenta Paderbornensia (1669 und 1672) - Süßmann, Johannes (Monumenta. Erinnerungsorte zwischen Weser und Lippe. Die Monumenta Paderbornensia des Ferdinand von Fürstenberg)

Training matters: Heading incidence and characteristics in children's and youth football (soccer) players - Reeschke, Rebecca; Haase, Franziska Katharina; Dautzenberg, Lena; Krutsch, Werner; Reinsberger, Claus (Scandinavian Journal of Medicine & Science in Sports)
Abstract Objective Concerns about short‐ and long‐term consequences of repetitive heading contributed to heading restrictions in youth football in some countries. This prospective longitudinal cohort study aims to describe heading exposure in children's and youth football over two seasons using standardized video analysis. Methods All matches and training sessions of a male Under‐11 ( n = 29), Under‐15 ( n = 28), Under‐19 ( n = 38), and female Under‐17 ( n = 39) team were videotaped during the seasons 2019–2020 and 2020–2021. Heading frequencies and characteristics were analyzed. Individual heading exposure is presented as average incidence rates (IR) per 1000 match/training hours. Results In 275 matches and 673 training sessions, 22 921 headers were observed. Heading IR per player in matches was 1256 (Under‐11 m), 1608 (Under‐15 m), 1050 (Under‐17 f), and 1966 (Under‐19 m). In training sessions, IR per player was 739 (Under‐11 m), 2206 (Under‐15 m), 1661 (Under‐17 f), and 1419 (Under‐19 m). Five Under‐15 males headed the ball five to eight times per training on average. Most headers were performed without heading duels. Flight distance was predominantly 5–20 m (54%) in matches and <5 m (65%) in training. While head impact location most frequently was at frontal areas, one‐third of all headers in Under‐11 in matches hit temporal, parietal, and occipital parts of the head. Conclusion Heading incidence was low in the youngest age group, whereas (predominantly five) Under‐15 males showed very high heading exposures in training. In assessment and regulation of heading burden, training sessions and individual heading behavior should specifically be addressed. Recommendations for heading the ball in practice should account for individual and age‐related differences.
Keywords: Physical Therapy; Sports Therapy and Rehabilitation; Orthopedics and Sports Medicine

Quasi-In Situ Localized Corrosion of an Additively Manufactured FeCo Alloy in 5 Wt Pct NaCl Solution - Pramanik, Sudipta; Krüger, Jan Tobias; Schaper, Mirko; Hoyer, Kay-Peter (Metallurgical and Materials Transactions A)
Abstract FeCo alloys are important materials used in pumps and motors in the offshore oil and gas drilling industry. These alloys are subjected to marine environments with a high NaCl concentration, therefore, corrosion and catastrophic failure are anticipated. So, the surface dissolution of additively manufactured FeCo samples is investigated in a quasi- in situ manner, in particular, the pitting corrosion in 5.0 wt pct NaCl solution. The local dissolution of the same sample region is monitored after 24, 72, and 168 hours. Here, the formation of rectangular and circular pits of ultra-fine dimensions (less than 0.5 µ m) is observed with increasing immersion time. In addition, the formation of a corrosion-inhibiting surface layer is detected on the sample surface. Surface dissolution leads to a change in the surface structure, however, no change in grain shape or grain size is noticed. The surface topography after local dissolution is correlated to the grain orientation. Quasi- in situ analysis shows the preferential dissolution of high-angle grain boundaries (HAGBs) leading to a change in the fraction of HAGBs and low-angle grain boundaries fraction (LAGBs). For the FeCo sample, a potentiodynamic polarisation test reveals a corrosion potential (E corr ) of − 0.475 V referred to the standard hydrogen electrode (SHE) and a corrosion exchange current density (i corr ) of 0.0848 A/m 2 . Furthermore, quasi- in situ experiments showed that grains oriented along certain crystallographic directions are corroding more compared to other grains leading to a significant decrease in the local surface height. Grains with a plane normal close to the $$\langle {1}00\rangle$$ ⟨ 100 ⟩ direction reveal lower surface dissolution and higher corrosion resistance, whereas planes normal close to the $$\langle {11}0\rangle$$ ⟨ 110 ⟩ direction and the $$\langle {111}\rangle$$ ⟨ 111 ⟩ direction exhibit a higher surface dissolution.
Keywords: Metals and Alloys; Mechanics of Materials; Condensed Matter Physics

Routing in Hypergraphs - Deppe, Volker

Citizen Science: Laien-Partizipation an Forschung - Göbel, Claudia; Henke, Justus; Mauermeister, Sylvi; Pasternack, Peer (Wissenschaftskommunikation, neu sortiert.)

Contrastiveness in the context of action demonstration: an eye-tracking study on its effects on action perception and action recall - Singh, Amit; Rohlfing, Katharina J. (Proceedings of the Annual Meeting of the Cognitive Science Society 45 (45))
The study investigates two different ways of guiding the addressee of an explanation - an explainee, through action demonstration: contrastive and non-contrastive. Their effect was tested on attention to specific action elements (goal) as well as on event memory. In an eye-tracking experiment, participants were shown different motion videos that were either contrastive or non-contrastive with respect to the segments of movement presentation. Given that everyday action demonstration is often multimodal, the stimuli were created with re- spect to their visual and verbal presentation. For visual presentation, a video combined two movements in a contrastive (e.g., Up-motion following a Down-motion) or non-contrastive way (e.g., two Up-motions following each other). For verbal presentation, each video was combined with a sequence of instruction descriptions in the form of negative (i.e., contrastive) or assertive (i.e., non-contrastive) guidance. It was found that a) attention to the event goal increased for this condition in the later time window, and b) participants’ recall of the event was facilitated when a visually contrastive motion was combined with a verbal contrast.
Keywords: Attention; negation; contrastive guidance; eye-movements; action understanding; event representation

Dialogical Functions of You-Narration in Auto/Biography: Anne Harich’s “Wenn ich das gewußt hätte…”: Erinnerungen an Wolfgang Harich (2007) - Mildorf, Jarmila (Zagadnienia Rodzajów Literackich)

Fünf Thesen zur Untersuchung des Textsortenwandels - Schuster, Britt-Marie; Haaf, Susanne (Historische Textmuster im Wandel. Neue Wege zu Ihrer Erschließung)

Fragen stellen in Pressetextsorten - Schuster, Britt-Marie; Thielert, Frauke; Haaf, Susanne (Historische Textmuster im Wandel. Neue Wege zu ihrer Erschließung)